The sylvian keyhole approach for surgical clipping of middle cerebral artery aneurysms: Technical nuance to the minipterional craniotomy - Rychen, Jonathan; Saemann, Attill; Gehweiler, Julian E.; Roethlisberger, Michel; Soleman, Jehuda; Hutter, Gregor; Müller-Gerbl, Magdalena; Mariani, Luigi; Guzman, Raphael (Frontiers in Surgery, 2022)
Background: The minipterional (MPT) craniotomy is a workhorse approach for clipping of middle cerebral artery (MCA) aneurysms. Because it aims to reach the skull base, traction on the temporal muscle is required. As a result, patients may suffer from transient postoperative temporal muscle discomfort. The sylvian keyhole approach (SKA) represents an alternative craniotomy for the clipping of MCA aneurysms. The aims of this study are to describe the operative technique of the SKA and to discuss the benefits and disadvantages compared to the MPT craniotomy. Methods: In this technical note, we report the experience gained with the SKA. This experience was acquired with virtual reality, 3D-printed models, and anatomical dissections. We also present two clinical cases. Results: The SKA is centered on the distal sylvian fissure and tailored toward the specific MCA aneurysm. Traction to the temporal muscle is not necessary because access to the skull base is not sought. With the SKA, dissection of the MCA is performed from distal to proximal, aiming for a proximal control at the level of the M1-segment. The limen insulae was identified as a key anatomical landmark for approach selection. The SKA offers good surgical maneuverability when the aneurysm is located at the level or distal to the limen. The MPT craniotomy, however, remains the most appropriate approach when the aneurysm is located proximal to the limen. Conclusion: The SKA represents a feasible and innovative alternative approach to the MPT craniotomy for surgical clipping of unruptured MCA aneurysms located at the level or distal to the limen insulae.